Sedentary subjects have higher PAI-1 and lipoproteins levels than highly trained athletes - Lira Fabio S; Rosa Jose C; Lima-Silva Adriano E; Souza Hélio A; Caperuto Erico C; Seelaender Marília C; Damaso Ana R; Oyama Lila M; Santos Ronaldo VT (Diabetology & Metabolic Syndrome, 2010)
Abstract Physical exercise protects against the development of cardiovascular disease, partly by lowering plasmatic total cholesterol, LDL-cholesterol and increased HDL-cholesterol levels. In addition, it is now established that reduction plasmatic adiponectin and increased C-reactive protein (CRP) and plasminogen activator inhibitor-1 (PAI-1) levels play a role in the maintenance of an inflammatory state and in the development of cardiovascular disease. This study aimed to examine plasma lipid profile and inflammatory markers levels in individual with sedentary lifestyle and/or highly trained athletes at rest. Methods: Fourteen male subjects (sedentary lifestyle n = 7 and highly trained athletes n = 7) were recruited. Blood samples were collected after an overnight fast (~12 h). The plasmatic lipid profile (Triglycerides, HDL-cholesterol, LDL-cholesterol, total cholesterol, LDL-oxidized and total cholesterol/HDL-c ratio), glucose, adiponectin, C - reactive protein and PAI-1 levels were determined. Results: Total cholesterol, LDL-cholesterol, TG and PAI-1 levels were lower in highly trained athletes group in relation to sedentary subjects (p < 0.01). In addition, we observed a positive correlation between PAI-1 and total cholesterol (r = 0.78; p < 0.0009), PAI-1 and LDL-c (r = 0.69; p < 0.006) and PAI-1 and TG levels (r = 0.56; p < 0.03). The plasma concentration of adiponectin, CRP, glucose, HDL-cholesterol and total cholesterol/HDL-c ratio levels were not different. These results indicate that lifestyle associated with high intensity and high volume exercise induces changes favourable in the lipid profile and PAI-1 levels and may reduce risk cardiovascular diseases.